Masterclass professional studio photography - Savini, Dennis (Santa Barbara, CA Rocky Nook, 2012)
"This book provides a comprehensive workshop on studio photography aimed at aspiring professionals. Richly illustrated, it covers an array of photographic subjects including still life, industry, technology, food, jewelry, portraiture, and more. The first part of the book focuses on concepts of studio planning, lighting, perspective, and camera and lens choices. The workshops that follow include 50 full-page photographic masterpieces, each with a detailed description of how the image was created. Author Dennis Savini walks the reader through all of the steps that led to each of his magnificent studio shots as he describes and illustrates the camera and equipment specs, studio design and setup, lighting, and post-processing. All of this information is communicated in a clear and simple manner and includes example images, diagrams of studio setups and lighting arrangements, and computer screenshots. Savini reveals the tips, tricks, and secrets he has learned throughout his many years as a professional photographer and teacher"--
Studio photography -- Product photography -- Still life -- Industry & technology -- Cosmetics & accessories -- Watches & jewelry -- Drinks -- Food -- Portraits
Includes index
1
Keywords: Commercial photography; PHOTOGRAPHY / Commercial; PHOTOGRAPHY / General; PHOTOGRAPHY / Reference; PHOTOGRAPHY / Techniques / Digital (see also COMPUTERS / Digital Media / Photography); PHOTOGRAPHY / Techniques / Equipment; PHOTOGRAPHY / Techniques / General; PHOTOGRAPHY / Techniques / Lighting; Photography -- Studios and dark rooms; Still-life photography